Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1590/s0103-50532011001100010
|View full text |Cite
|
Sign up to set email alerts
|

Phenylpropanoid substituted flavan-3-ols from Trichilia catigua and their in vitro antioxidative activity

Abstract: O novo flavan-3-ol contendo um substituinte fenilpropanoide apocinina E, juntamente com oito substâncias conhecidas, epicatequina, procianidina B2, procianidina B4, procianidina C1, cinchonaína Ia, cinchonaína Ib, cinchonaína IIb e cinchonaína IIa foram isoladas a partir do extrato acetona-H 2 O das cascas secas de Trichilia catigua. As substâncias cinchonaína Ib e cinchonaína IIb foram reavaliadas em relação à sua estereoquímica. Todas as substâncias foram caracterizadas por análises espectroscópicas incluind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
27
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 21 publications
(46 reference statements)
5
27
0
Order By: Relevance
“…From the preliminary results of the chemical analyses, it was possible to determine the chemical marker for each plant drug. These data were corroborated from literature sources (Oliveira et al, 1984apud Osório & Martins, 2004Kawashty et al, 1994;Müller & Kasper, 1996;Veneziani & Oliveira, 1999;Pereira et al, 2000;De Souza, 2002;Pizzolatti et al, 2002;Yang & Lambert, 2003;Araújo-Junior et al, 2004;Polydoro et al, 2004;Chan et al, 2007;Marques et al, 2007;Resende et al, 2011;Manian et al, 2008;Silva et al, 2010).…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…From the preliminary results of the chemical analyses, it was possible to determine the chemical marker for each plant drug. These data were corroborated from literature sources (Oliveira et al, 1984apud Osório & Martins, 2004Kawashty et al, 1994;Müller & Kasper, 1996;Veneziani & Oliveira, 1999;Pereira et al, 2000;De Souza, 2002;Pizzolatti et al, 2002;Yang & Lambert, 2003;Araújo-Junior et al, 2004;Polydoro et al, 2004;Chan et al, 2007;Marques et al, 2007;Resende et al, 2011;Manian et al, 2008;Silva et al, 2010).…”
Section: Resultssupporting
confidence: 77%
“…Deionized water was prepared with a Millipore Milli-Q Plus system (Millipore, Bedford, MA, USA). Hydroquinone, epicatechin, catechin, caffeic acid, chlorogenic acid, gallic acid, o-coumaric acid, quercetin, coumarin, lupeol, and rutin (Sigma, USA), isoastilbin and cinchonain Ib (isolated and certified by spectroscopic methods at the Pharmaceutical Biology Laboratory of the Universidade Estadual de Maringá; Marques et al, 2007;Resende et al, 2011), and epicatechin-3-Ogallate (kindly provided by Dr. Frank Petereit, Institute for Pharmaceutical Biology and Phytochemistry of the Universität Münster, Germany; Danne et al, 1994) of the highest grade (purity >99.0%) were used as external standards.…”
Section: Reagents Standard Solutions and Materialsmentioning
confidence: 99%
“…Juss., known as "catuaba" in Brazil, has been popularly used as a tonic for fatigue, impotence and memory deficits. It has been demonstrated that the ethyl-acetate fraction (EAF) of T. catigua has antioxidant and anti-inflammatory effects [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, our group reported the antioxidant capacity of EAF from the bark of T. catigua, where nine polyphenolic constituents with antioxidant effects were found [11,13]. Furthermore, subchronic treatment with EAF promoted an antidepressant effect as well as increased hippocampal cell proliferation in mice [12].…”
Section: Introductionmentioning
confidence: 99%
“…It is used in Brazilian popular medicine as a tonic for the treatment of fatigue, stress, impotence, and memory deficits, mainly due to its ability to inhibit or protect against free radicals. The crude extracts and isolated compounds (epicatechin, cinchonains Ia, Ib, IIa, IIb, catiguanins A and B, apocynin E, and procyanidins B2 and C1) from the bark of T. catigua show antioxidant activity toward the free radical 2,2-diphenyl-2-picrylhydrazyl (DPPH), and reduction of the Fe 3+ / ferricyanide complex to the ferrous form [9][10][11][12][13][14] .…”
Section: Introductionmentioning
confidence: 99%